Sistema de iluminação distribuída utilizando LED's acionados por dois conversores flyback integrados - Oliveira, Alessandro André Mainardi de (2007)
This dissertation describes the design and implementation of an emergency lighting system using Light Emitting Diodes (LED s). The system is composed by two integrated converters working as battery charger and LED s supplying. Power LED s were used, due to their high luminous flux and opening angle of 160°. System control and management are done through a microcontroller. The features of light emitting diodes are discussed in this work. The system is based on both Brazilian and international current emergency lighting systems standards, NBR10898, 1999 and IEEE Std 446, 1995, respectively